2010
DOI: 10.1007/s00520-010-1028-1
|View full text |Cite
|
Sign up to set email alerts
|

Prospective comparison of the prognostic utility of the Mini Mental State Examination and the Montreal Cognitive Assessment in patients with brain metastases

Abstract: Our results indicate that the MoCA is a superior prognostic indicator than the MMSE. Furthermore, given its superior sensitivity and better correlation with quality of life, the MoCA should be preferentially chosen in clinical practice and trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
29
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 52 publications
(32 citation statements)
references
References 38 publications
0
29
3
Order By: Relevance
“…In the last decade, the Montreal Cognitive Assessment (MoCA) (11) screening tool has been increasingly favored over the MMSE as it has been shown to have greater sensitivity for detecting cognitive dysfunction. This has been shown in patients with brain tumors (12) and brain metastases (13), as well as in other neurological conditions including stroke (14), sub-arachnoid hemorrhages (SAHs) (15), and silent cerebral infarcts (16). Bernstein et al investigated the psychometric properties of the MoCA in three diverse brain pathologies and concluded that it was reliable in detecting cognitive dysfunction as well as having the benefit of not fatiguing the patient (17).…”
Section: Introductionmentioning
confidence: 92%
“…In the last decade, the Montreal Cognitive Assessment (MoCA) (11) screening tool has been increasingly favored over the MMSE as it has been shown to have greater sensitivity for detecting cognitive dysfunction. This has been shown in patients with brain tumors (12) and brain metastases (13), as well as in other neurological conditions including stroke (14), sub-arachnoid hemorrhages (SAHs) (15), and silent cerebral infarcts (16). Bernstein et al investigated the psychometric properties of the MoCA in three diverse brain pathologies and concluded that it was reliable in detecting cognitive dysfunction as well as having the benefit of not fatiguing the patient (17).…”
Section: Introductionmentioning
confidence: 92%
“…In fact, cognitive impairment in these patients is more common than physical disability, in contrast to other focal neurological disorders such as cerebral vascular accidents [7]. Detection of cognitive impairment in this population is clinically important because it is an independent predictor of survival and disease recurrence [1,2,[8][9][10][11]. In addition, cognitive function may be correlated with quality of life (QoL), and individuals who are cognitively impaired may improve their QoL through rehabilitation.…”
Section: Introductionmentioning
confidence: 98%
“…Traditionally, prognostication for patients with HGGs has been based on factors such as age, performance status, cognitive function, tumor grade, and extent of resection [1,2].…”
Section: Introductionmentioning
confidence: 99%